EXPLORING THE RELATIONSHIP BETWEEN THE INFECTION OF C.PNEUMONIAE AND CORONARY ARTERY DISEASE - Al-khatib, Ahed J; Al-Alawneh, Majdi (European Scientific Journal, ESJ, 2013)
Atherosclerosis is considered an inflammatory disease, accordingly, there has been extensive research to determine whether microbial infections possibly contribute and maintain this inflammatory response. Chlamydia pneumoniae (C. pneumoniae), a common causative agent of respiratory tract infections, was associated with coronary artery disease (CAD) diseases. C. pneumoniae is a gram-negative bacterium which resembles viruses in terms of obligate intracellular growth. C. pneumoniae is able to infect several cell types, including circulatory monocytes, and by using monocytes as a vector, C. pneumoniae can disseminate from the lungs into extrapulmonary sites, including the subendothelium space of the arterial wall. In addition to inflammation lesion, development in the arterial wall requires macrophage transformation foam cells in the presence of an atherogenic cholesterol source like low-density lipoprotein (LDL) cholesterol. The present investigation studied the relationship and prevalence of C. pneumoniae in patient with CAD who underwent to angiography. In this study, 130 patients were enrolled. Blood samples were taken from each patient, data collection, ELISA for IgG antibody and PCR for OMP1 gene have been carried out. The results showed that the prevalence of C. pneumoniae among the study sample was 56 out of 130 (43.1%) when ELISA is applied. However, prevalence of C. Pneumoniae decreased to 36 samples (27.7%) when the previous results were confirmed using PCR. This indicates that 65% of the ELISA positive samples were also PCR positive. The patients with CAD were considered as clinical symptomatic for C. pneumoniae, indicated that the organism used monocytes and macrophages as a vector, which lead to the acceleration of the atherosclerosis process. The total number of the patients, who ﻿did not have any risk factor were 28 out of 130 patients (21.5 %). Twenty samples out of these 28 were positive in both ELISA and PCR (71.4 %),4 samples were positive in ELISA and negative in PCR(14.3 % ), and 4 samples were negative in both ELISA and PCR (14.3%). C. pneumoniae infection is considered as independent risk factor for CAD or atherosclerosis process. This study showed that there is an association between C. pneumoniae and CAD, between C. pneumoniae and diabetes, hypertension and smoking. On the other hand, it was clear that there is no association between C. pneumoniae and age, sex, living area, residence area, job, health food, rest pain, intermittent claudicating, obesity, hyperlipidemia, and environmental exposure.